Relationship between physical activity and quality of life in youth during the COVID-19 pandemic - Pablo Valdés-Badilla (ECIMED, 2021)
Introduction: The COVID-19 pandemic has generated social distancing, causing a decrease in the practice of physical activity and a lower health-related quality of life. Objective: To relate the level of physical activity with health-related quality of life in youth, during COVID-19 lockdown. Methods: Cross-sectional study that evaluated 184 students (61,4 % female) with a mean age of 13,97 + 1,69 years, residing in the Maule region, Chile. Two self-application surveys were applied, with the short version of the International Physical Activity Questionnaire and the valid version in the Chilean population of the KIDDO-KINDL. Results: There was a direct and significant correlation between the total time of mild physical activity with self-esteem (p= 0,043) and, between the total sitting time with emotional well-being (p= 0,025), self-esteem (p= 0,014), school (p= 0,031), and total quality of life score (p= 0,006) for the total sample. Only females showed a correlation (p< 0,05) between total time sitting with family, school, and total quality of life score. In addition, significant differences (p< 0,05) were found in the total time of moderate physical activity, school, and total quality of life score in favor of males. Conclusion: There is a relationship between the total time of physical activity with self-esteem and between the total sitting time with emotional well-being, self-esteem, school, and total quality of life score in youth during COVID-19 lockdown.